Waste mitigation and resource recovery from food industry wastewater employing microalgae-bacterial consortium. (May 2022) - Sirohi, Ranjna; Joun, Jaemin; Lee, Ji Young; Yu, Byung Sun; Sim, Sang Jun
Graphical abstract: Highlights: Aerobic biofilm reactor are preferable for dairy industry wastewater treatment. Combined anaerobic and aerobic sludge increases COD removal for starch wastewater. Mussel-bacteria-microagal consortia suitable for aquaculture wastewater treatment. Scale-up studies required for wastewater treatment for microalgae-bacteria consortium. Abstract: Wastewater generated by the food industry is rich in nitrogen and phosphorus with possible presence of heavy metals. Physical and chemical methods of treatment, although effective, are expensive and may cause secondary environmental pollution damaging aquatic and human life. Traditional biological methods are eco-friendly and cost-effective but involve standalone microorganisms that pose risk of contamination and are not as effective. This review discusses the application of novel microalgal-bacterial consortium as a solution for the resource recovery and treatment of dairy, starch and aquaculture wastewater. Use of biofilm reactors containing anaerobic and aerobic sludge has shown 80–90% and > 90% COD and nutrient removal efficiency in treatment of dairy and starch processing wastewater, respectively. The treatment of aquaculture processing wastewater can be challenging due to high sality and requires salt-tolerant bacteria-microalgae consortium. In this regard, the identification of dominant microalgae and bacteria using 16S rRNA and 18S rRNA genes is recommended.